Pentingnya Pemahaman Orang Tua Terhadap Pola Asuh pada Anak Usia Dini - Tahera, Sita; Wulandari, Hayani (Peneliti.net, 2024)
A child's personality, habits and social life are determined by several factors such as genetic factors and environmental factors. Parents, as the first environment a child encounters, will make a major contribution to the formation of the child's personality. Therefore, every family has a parenting model and methods for providing stimulus and education so that their children can have good personalities and development and growth. Parenting patterns and goodrelationships between children and parents will show how well parents understand parenting patterns and apply them. The aim of this research is to find out whether parents are aware of the importance of understanding parenting styles and the impact of the parenting styles used on their children, and whetherparents are aware of the impact of the parenting styles they provide on children's development. The method used in the research is a descriptive method with a quantitative approach. With research subjects 31 people who were married. 14 people are married and have children and 17 people are married and do not have children. The data collection method used was a questionnaire. The results of the research show that parents and prospective parents are now aware of the importance of understanding parenting styles for early childhood. Of the 31 subjects, 100% were aware of the importance of understanding parenting styles on the growth and development of early childhood. From the results of the analysis it can also be concluded that parenting knowledge has now spread widely on social media, making it easier for parents and prospective parents to access it.Keywords: Parenting patterns, parents, early childhood, parenting